RESPECTING CHILDREN’S RIGHTS THROUGH THE INSTITUTION OF MINORS PROTECTION BY PARENTS - Mădălina TOMESCU; Andrada Mihaela TRUȘCĂ (Challenges of the Knowledge Society, 2014)
Every society hopes and expects that the younger generation, meaning children, grow and become capable and responsible citizens that contribute to the welfare of the community. However in the whole world, children are denied the most elementary rights of normal development, active participation and even the survival. Therefore, both at international level and national level have been taken measures to respect children's rights and thus to protect them. Parental care is the care of the juvenile legal means consisting of all rights and duties relating to both person and property belonging of the child by both parents equally. The exercise of parental care is performed under control of the state, represented by the guardianship court. On how to exercise parental care usually is an accomplished both parents jointly and equally. But there are certain situations where it is not possible to apply this rule, given that one of the parents is impossible to exercise their rights and duties incumbent. In these cases exception is exercising parental care by one of the parents.